2018
DOI: 10.1038/s41598-017-18854-1
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, waist circumference, and waist-to-height ratio for prediction of multiple metabolic risk factors in Chinese elderly population

Abstract: The purpose of this study was to compare the predictive ability of five obesity indices, including body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), waist-to-hip ratio (WHpR) and body adiposity index (BAI), to predict multiple non-adipose metabolic risk factors, including elevated blood pressure (BP), elevated fasting plasma glucose (FPG), elevated triglyceride (TG), reduced high-density lipoprotein cholesterol (HDL-C), elevated serum uric acid (SUA) and non-alcoholic fatty liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 31 publications
6
40
2
3
Order By: Relevance
“…The World Health Organization Working Group on Obesity recommends WC cutoff values of 85 cm for men and 80 cm for women, which are lower than those determined here (95.5 and 88.5 cm for middle-aged and elderly men, respectively; and 83.5 and 83.5 cm for middle-aged and elderly women, respectively). Our BMI ranges (23.86-24.01 for men and 24.08-23.57 for women) were similar to those in previous studies (22.65-24.12 for men and 23.53-27.7 for women) [17,31,32,35], and the same was true for WHtR (0.54-0.55 for men and 0.51-0.52 for women in the present study vs 0.47-0.54 and 0.47-0.54, respectively, in previous reports) [17,24,31,32,35,36,[38][39][40]. Notably, values obtained in a study conducted in Spain (WC, 90.5 cm; BMI, 26.6; WHtR, 0.54 for both sexes) [34]were much higher than those in Asian cohorts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The World Health Organization Working Group on Obesity recommends WC cutoff values of 85 cm for men and 80 cm for women, which are lower than those determined here (95.5 and 88.5 cm for middle-aged and elderly men, respectively; and 83.5 and 83.5 cm for middle-aged and elderly women, respectively). Our BMI ranges (23.86-24.01 for men and 24.08-23.57 for women) were similar to those in previous studies (22.65-24.12 for men and 23.53-27.7 for women) [17,31,32,35], and the same was true for WHtR (0.54-0.55 for men and 0.51-0.52 for women in the present study vs 0.47-0.54 and 0.47-0.54, respectively, in previous reports) [17,24,31,32,35,36,[38][39][40]. Notably, values obtained in a study conducted in Spain (WC, 90.5 cm; BMI, 26.6; WHtR, 0.54 for both sexes) [34]were much higher than those in Asian cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…The cutoff values with the best predictive capacity for high PWV in the present work based on sensitivity and speci city differed from those reported in studies of hypertension in Asian populations; the ranges were 82.70-85.2 for men and 77.5-83.5 for women [17,31,32,35,36]. The World Health Organization Working Group on Obesity recommends WC cutoff values of 85 cm for men and 80 cm for women, which are lower than those determined here (95.5 and 88.5 cm for middle-aged and elderly men, respectively; and 83.5 and 83.5 cm for middle-aged and elderly women, respectively).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Although many authors have produced specific WHtR boundary values for populations (24,27,61,62) , many suggest that the simple boundary value of 0•5 can be used to indicate increased risk and used universally for primary screening (29) . Since it was first advocated in 2006 (63) , the simple message 'Keep your waist to less than half your height' has been recommended often (20,34,(64)(65)(66) .…”
Section: Very Simple Screening Based On Waist-to-height Ratio 0•5: Thmentioning
confidence: 99%
“…Body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), are some of the anthropometric properties that are used to predict Department of Physiology, Faculty of Medicine, Van Yuzuncu Yil University, 65080, Van, Turkey. metabolic risk factors (Gu et al, 2018). A previous study investigated the relationship between the 2D:4D and cardiovascular risk factors and MetS indices among adults and suggested that 2D:4D is a proxy for heart relateddisease in Ilorin (Oyeyemi et al).…”
Section: Introductionmentioning
confidence: 99%